2022
DOI: 10.1186/s12882-022-02869-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of telehealth interventions added to peritoneal dialysis-care: a systematic review

Abstract: Background Telehealth could potentially increase independency and autonomy of patients treated with peritoneal dialysis (PD). Moreover, it might improve clinical and economic outcomes. The demand for telehealth modalities accelerated significantly in the recent COVID-19 pandemic. We evaluated current literature on the impact of telehealth interventions added to PD-care on quality of life (QoL), clinical outcomes and cost-effectiveness. Methods An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Poor BP control is an independent risk factor for graft failure and has unfavorable CV events for the recipient [84,85] . One study [86] identified HBPM to have a better correlation with ABPM than with OBPM in kidney recipients between 1 and 10 years after transplantation. Put together, these studies support the use of HBPM in patients receiving KRT and suggest benefits if HBPT is utilized, given the additional management support that will be made available.…”
Section: Home Bp Telemonitoring In Ckd Populationsmentioning
confidence: 99%
“…Poor BP control is an independent risk factor for graft failure and has unfavorable CV events for the recipient [84,85] . One study [86] identified HBPM to have a better correlation with ABPM than with OBPM in kidney recipients between 1 and 10 years after transplantation. Put together, these studies support the use of HBPM in patients receiving KRT and suggest benefits if HBPT is utilized, given the additional management support that will be made available.…”
Section: Home Bp Telemonitoring In Ckd Populationsmentioning
confidence: 99%
“…Within the literature on telehealth services in home dialysis patients, telehealth is a broad term for a vast variety of interventions in which digital applications are used in patient care. A systematic review of telehealth interventions within the context of home dialysis care found that telehealth interventions such as remote monitoring, video‐assisted dialysis, internet‐based instant messaging and nurse‐led postdischarge telephone support might reduce hospitalisation rates, the number of in‐person visits and improve patient satisfaction in home peritoneal dialysis patients (Biebuyck et al, 2022). Qualitative studies reported that telehealth remote monitoring is acceptable by patients (Scofano et al, 2022) and has the potential to assist in creating a sense of security for them and others (Rygh et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…mHealth delivers pre-established health services and provides guidance regarding the PD procedure and disease-related information in real time through features such as browsing, text messaging, communication, and videos [ 11 , 14 , 15 ]. mHealth apps enable the collection of patient health-related data, including access to personal medical records, obtaining nutritional or dietary information, receiving treatment-related details, offering disease-related information, understanding health status, tracking exercise activities, weight, and dietary habits, monitoring medication dosage, recording blood pressure, and providing convenience and efficiency for patients with PD [ 3 , 4 , 6 , 9 , 14 , 16 , 17 , 18 , 19 ]. Additionally, some mHealth apps have interactive features that allow patients to communicate immediately with physicians or nurses when difficulties arise [ 6 ].…”
Section: Introductionmentioning
confidence: 99%